Gestures During Knapping: A Two-perspective Approach to Pleistocene Technologies. (3rd April 2019) - Cueva-Temprana, Arturo; Lombao, Diego; Morales, Juan Ignacio; Geribàs, Nuria; Mosquera, Marina
ABSTRACT: Understanding the evolution of technological complexity is a major goal in the study of prehistoric lithic industries. This has led to the development of different methods to examine both archaeological items and their production processes. These methods have attempted to segment the actions that form an operational sequence, usually with the aim of quantifying the complexity involved in lithic knapping. However, to date, no study has been capable of cataloguing these actions to the point of characterizing the elements that comprise them. In this work, we propose an approach to identify the smallest unit of any knapping action: the manual gesture. Our goal is to provide a homogeneous language allowing the characterization and quantification of 1) the variability between lithic industries, and 2) the evolution of technological complexity, from both synchronic and diachronic view. As a proof-of-concept, we designed a pilot experiment to characterize the manual gestures involved in making choppers, chopping-tools and handaxes. Our results confirm the reliability of this approach. In addition, it points to the existence of a gestural primordial core that lasted throughout the Oldowan and the Acheulean –as knapping sequences increased in complexity- and the potential to identify some specific traits of the individual knappers.